Treatment of ameloblastoma - Fernando Vagner Raldi; Rubens Guimarães-Filho; Michelle Bianchi de Moraes; Ana Cristina Claro Neves (Faculdade São Leopoldo Mandic, 2010)
Ameloblastoma is a benign odontogenic tumor of epithelial origin, with slow growth, frequently found in the mandible or maxilla. The symptoms are unnoticeable, rarely being perceived by the patient in the initial stages, and are sometimes diagnosed by chance in routine radiographic exams. Clinically, it is a hardened curvature that grows slowly, and the regional mucosa remains with the normal appearance. There is rarely a solution of continuity or infection. The ameloblastoma invades the spaces between the trabeculated bones without reabsorbing them, and expands the compact bone without invading it, however, it may propagate through the mandibular canal. It has been given this name due to its similarity to the cells of the enamel organ and it has a unique biological behavior that leads to controversy with regard to the best form of treatment. This clinical case describes the case of a unicystic ameloblastoma located in the left retromandibular region with eight years of follow-up. Clinical and radiographic diagnosis was confirmed through the histopathologic exam. Treatment proposed was enucleation without marginal dissection.